PENGARUH PENDAPATAN NON-BUNGA, EFISIENSI BANK DAN MASKULINITAS TERHADAP RISIKO BANK - Ristitriani, Nike; Ismanto, Hadi (Unitri Press, 2025)
This research aims to analyze the influence how non-interest income, bank efficiency, and masculinity affect bank risk in Indonesian commercial banks listed on the Indonesian stock exchange (IDX) for the 2019-2023 period. Bank risk measurement is proxied using the z-score value. This research type is quantitative research and the data used secondary data from Indonesian commercial banks' financial reports for the 2019–2023 period that are published on the Indonesia Stock Exchange (IDX). Using a saturation sampling technique, 47 Indonesian commercial banks were included in the sample for the 2019–2023 period. Hypothesis testing in this study used data panel regression analysis with a fixed effect model. This research findings show that non-interest income can reduce bank risk, bank efficiency can reduce bank risk, and masculinity can increase bank risk.